2007
DOI: 10.1590/s1678-77572007000200004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a bonding resin layer associated with a self-etching adhesive system on the bond strength of indirect restorations

Abstract: The aim of this study was to evaluate the influence of a low-viscosity bonding resin applied over a self-etching adhesive system on the microtensile bond strength (μTBS) of indirect restorations. Comparisons were made using One Up Bond F (OB) self-etching adhesive system, Single Bond (SB) one-bottle adhesive system and Scotchbond Multi Purpose Plus (SMP) bonding component. Thirty bovine incisors were extracted and decoronated at the cementoenamel junction. The labial surfaces were ground so that superficial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Some of the limitations of the self-etch adhesive tested include the following: no capability for dual polymerization, which can be desirable for indirect adhesive restorations, and difficulty in preventing the acid resin from splashing onto adjacent teeth or soft tissue during air-drying. Castro, et al 7 (2007) concluded that the self-etch adhesive system was significantly more efficient in dentin than in enamel, while the one-bottle system was significantly more efficient in enamel when compared to the self-etch adhesive system.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the limitations of the self-etch adhesive tested include the following: no capability for dual polymerization, which can be desirable for indirect adhesive restorations, and difficulty in preventing the acid resin from splashing onto adjacent teeth or soft tissue during air-drying. Castro, et al 7 (2007) concluded that the self-etch adhesive system was significantly more efficient in dentin than in enamel, while the one-bottle system was significantly more efficient in enamel when compared to the self-etch adhesive system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, peritubular dentin has been reported up to five times thinner in DT which leads to lower moisture (Mazzeo et al;Prabhakar et al, 2003;Stanlin et al, 2005;Cavalcanti et al, 2008;Chowdahary & Subba Reddy), as well as greater reactivity to acid conditioning (Nör et al, 1996). The stable adhesion between resin and dentin represents a fundamental requirement for clinical success and it depends on the proper interaction between the dental substrate, the adhesive system and the restoration (Castro et al, 2007). In agreement with García-Godoy & Donly (2002), a minimum bonding force of 17-20 MPa is necessary to withstand the contraction force of the composite resin in the enamel and dentin Therefore, the purpose of this research was to compare the bonding strength of total etch and self-etch adhesive systems on primary deciduous teeth as well as on permanent teeth.…”
Section: Introductionmentioning
confidence: 99%